Multi-functional mechanisms of immune evasion by the streptococcal complement inhibitor C5a peptidase. - Nicola N Lynskey; Mark Reglinski; Damien Calay; Matthew K Siggins; Justin C Mason; Marina Botto; Shiranee Sriskandan (PLoS Pathogens)
The complement cascade is crucial for clearance and control of invading pathogens, and as such is a key target for pathogen mediated host modulation. C3 is the central molecule of the complement cascade, and plays a vital role in opsonization of bacteria and recruitment of neutrophils to the site of infection. Streptococcal species have evolved multiple mechanisms to disrupt complement-mediated innate immunity, among which ScpA (C5a peptidase), a C5a inactivating enzyme, is widely conserved. Here we demonstrate for the first time that pyogenic streptococcal species are capable of cleaving C3, and identify C3 and C3a as novel substrates for the streptococcal ScpA, which are functionally inactivated as a result of cleavage 7 amino acids upstream of the natural C3 convertase. Cleavage of C3a by ScpA resulted in disruption of human neutrophil activation, phagocytosis and chemotaxis, while cleavage of C3 generated abnormally-sized C3a and C3b moieties with impaired function, in particular reducing C3 deposition on the bacterial surface. Despite clear effects on human complement, expression of ScpA reduced clearance of group A streptococci in vivo in wildtype and C5 deficient mice, and promoted systemic bacterial dissemination in mice that lacked both C3 and C5, suggesting an additional complement-independent role for ScpA in streptococcal pathogenesis. ScpA was shown to mediate streptococcal adhesion to both human epithelial and endothelial cells, consistent with a role in promoting bacterial invasion within the host. Taken together, these data show that ScpA is a multi-functional virulence factor with both complement-dependent and independent roles in streptococcal pathogenesis.